Towards the bryophyte flora of the Sutjeska National Park (the Republic of Srpska, Bosnia and Herzegovina) - Jovana Pantović; Đorđije Milanović; Ivana Janković; Marko Sabovljević (Glasnik Šumarskog Fakulteta Univerziteta u Banjoj Luci, 2017)
Old literature data together with recent field research were combined in order to present bryophyte checklist of the Sutjeska National Park. A total of 261 taxa were found within the park area, out of which 40 are liverwort and 221 moss taxa. Bearing in mind a huge lack of bryological research in Bosnia and Herzegovina during last decades, 41 species were refound after more than fifty years, and 92 new for the park area as well. Additionally, seven species are included in the candidate list of the new Red data book of European bryophytes. These are: Anoectangium aestivum, Buxbaumia viridis, Cinclidotus aquaticus, Fontinalis hypnoides, Orthotrichum patens, Pseudocampylium radicale and Schistidium helveticum.